100 ideas for teaching mathematics - 4 uthor (London: Continuum International Publishing Group, 2005)
Mike Ollerton provides 100 practical ideas on how to get students inspired about mathematics. All of his excellent ideas have been tried and tested in the classroom and provide children with a fun way to learn a very difficult subject.
A number of number puzzles--Puzzles to NAG (Number, Algebra and Graphs) your students with--Puzzles to cause your students to shape up--Puzzles to see how your students measure up--A few beer MAT's, some glue and a lot of imagination--SFGs, not perhaps as interesting as the BFG but nevertheless some giant-sized ideas for the classroom--Ideas for budding data handlers.
500-599
Keywords: Mathematics; Mathematics